2015
DOI: 10.1002/app.43214
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic resin‐crosslinked natural rubber/clay nanocomposites: Influence of clay loading and interfacial adhesion on strain‐induced crystallization behavior

Abstract: Nanocomposites of natural rubber (NR) and pristine clay (clay) were prepared by latex mixing, then crosslinked with phenolic resin (PhOH). For comparative study, the PhOH‐crosslinked neat NR was also prepared. Influence of clay loading (i.e., 1, 3, 5, and 10 phr) on mechanical properties and structural change of PhOH‐crosslinked NR/clay nanocomposites was studied through X‐ray diffraction (XRD), transmission electron microscopic (TEM), wide‐angle X‐ray diffraction (WAXD), tensile property measurement, and Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
5
21
0
Order By: Relevance
“…In our previous study on the chemical structure of PhOH‐crosslinked NR/clay nanocomposite, the FTIR spectrum revealed that the clay was chemically bound onto NR molecules through phenolic bridge during high temperature molding (at 180 °C), forming NR‐PhOH‐clay [product (A) in Scheme ]. So, in the NRPPNCs, the clay locally existed at the NR/PP interface could be reacted with the NR assisted by PhOH (dispersed at interface boundary as mentioned previously) in the NRPPNC blends, yielding intermediate NR‐PhOH‐clay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study on the chemical structure of PhOH‐crosslinked NR/clay nanocomposite, the FTIR spectrum revealed that the clay was chemically bound onto NR molecules through phenolic bridge during high temperature molding (at 180 °C), forming NR‐PhOH‐clay [product (A) in Scheme ]. So, in the NRPPNCs, the clay locally existed at the NR/PP interface could be reacted with the NR assisted by PhOH (dispersed at interface boundary as mentioned previously) in the NRPPNC blends, yielding intermediate NR‐PhOH‐clay.…”
Section: Resultsmentioning
confidence: 99%
“…The NR and PP was blended at 80/20 wt %. Based on previous study, the recommended dosage of clay into NR was at 5 phr. This concentration was then chosen for the preparation of NR/PP blend nanocomposites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade, since Arroyo et al . showed that organically modified clay causes an increment of more than 350% in the strength compared to unfilled NR (and > 300% compared to the same amount of CB), organoclays have been studied as a substitute for CB . A significant reduction in weight, preserved elasticity, and an enhancement in the strain‐induced crystallization (SIC) are additional advantages.…”
Section: Introductionmentioning
confidence: 99%